Effects of Ba2+/Sr2+ ratio on the microstructure, dielectric and ferroelectric properties of BaxSr(1−x)TiO3 films prepared by micro-arc oxidation. (2nd December 2021) - Wang, Min; Zuo, Xi; Li, Kang; Cao, Genghua
ABSTRACT: Bax Sr(1-x) TiO3 (BST) thin films are in situ deposited on a Ti matrix through the micro-arc oxidation technique, using a mixed aqueous solution of Ba(OH)2 8H2 O, Sr(OH)2 8H2 O and 0.05 M EDTA as the electrolyte. The influence of the Ba 2+ /Sr 2+ ratio on the phase composition, microstructure and properties of the BST thin films is investigated. Ba0.6 Sr0.4 TiO3, Ba0.5 Sr0.5 TiO3, and Ba0.4 Sr0.6 TiO3 thin films have a cubic phase, while Ba0.8 Sr0.2 TiO3 and Ba0.7 Sr0.3 TiO3 thin films have a tetragonal phase. When the concentration of Ba 2+ in the electrolyte surpasses that of Sr 2+, the width of micro-arc holes and the surface roughness of the film grow as the Ba 2+ concentration rises. Furthermore, the dielectric and ferroelectric properties of BST films are favorably connected with the surface morphology. When the Ba 2+ concentration is 0.06 M, the film has the best compactness and smoothness. In addition, the highest capacitance and lowest dielectric loss are achieved.